STEM-Based Learning Design of Local Potential Fermented Products in Virtual Classroom to Enhance Halal Literacy and Problem-Solving Skills: SYSTEMATIC LITERATURE - Rofiah Al-Zahro, Rd Indah (Science, Tecnology, Religious, Economic, and Social Humanitis (STREAS), 2024)
The aim of this research is to investigate STEM learning approaches in the context of local fermented products, strategies for increasing halal literacy, and developing problem solving. Research methods include systematic extraction and analysis of data from selected relevant articles. A literature search was carried out using related keywords between 07-18 April 2024. The research results show that effective learning designs for local fermented products take into account the unique characteristics of local products and the use of appropriate technology. Implementing a STEM approach in the virtual classroom has been shown to increase students' interest in STEM and their connection and communication skills. Integrating halal literacy in science learning is important to ensure understanding and making appropriate decisions in product consumption. Students' problem-solving skills, especially in the science context, can be improved through steps such as problem visualization, planning, and evaluation of results. In conclusion, the STEM approach and integration of halal literacy in teaching materials can increase learning effectiveness, while the development of problem solving skills can be done through structured methods and careful evaluation.